Effects of mutualistic and pathogenic soil mycobiota on forest ecosystem functioning: herbaceous phytometer growth on natural and sterilised soils. (August 2021) - Noreika, Norbertas; Pärtel, Meelis; Öpik, Maarja
Highlights: Herbaceous phytometer can serve as a fast indicator of forest soil productivity. Established habitat-specific fungal communities are crucial for forest functioning. Pathogens can harm plant growth in soils containing successional fungal communities. Mutualistic fungi can counterbalance negative pathogen effects on plant growth. Abstract: Knowledge of forest functioning is important for sustainable forest management and conservation. The growth variation of standardised plants (phytometers) can serve as a measure of ecosystem functions and provide a link with soil biotic and edaphic conditions. We aimed to test experimentally how forest edaphic conditions and different soil symbiotic fungal guilds, their diversity and relative abundance affect the growth of herbaceous phytometer. We explored whether phytometer growth differs among three types of soils: i) natural (established fungal community), ii) sterilised by gamma-irradiation, iii) sterilised and inoculated with natural soil (successional fungal communities). We analysed soil samples from 100 old-growth boreo-nemoral forests in Southern Estonia. We used environmental DNA to evaluate the diversity and relative abundance of the following fungal guilds: arbuscular mycorrhizal (AM), ectomycorrhizal (ECM), pathogenic, and saprotrophic fungi. Phytometer ( Hordeum vulgare ) was grown under controlled greenhouse conditions for three weeks on differently treated (natural, sterilised, inoculated) soils from all sites. Phytometer growth did not differ among treatments. Nevertheless, differently treated forest soils in interaction with fungal diversity measures often had a significant relationship with phytometer growth. Phytometer biomass was lower in successional communities with high pathogen diversity, which were counterbalanced by mutualists in established communities of natural soils. A positive relationship of phytometer growth with the diversity of forest-specific symbionts (ECM fungi) likely demonstrated the overall "health" of forest soils. The diversity of AM fungi was surprisingly negatively related to phytometer growth. However, the abundance of AM fungi showed a positive association with phytometer growth in successional communities. We demonstrate that phytometer growth was related to soil fungal diversity depending on the presence and successional status of soil biota. Our study highlights that a herbaceous phytometer can be a quick, undemanding and affordable indicator of the status of forest soil biota. Healthy habitat-specific fungal communities are crucial for forest functioning and should be considered in management.